Editor's Choice – Protamine Reduces Serious Bleeding Complications Associated with Carotid Endarterectomy in Asymptomatic Patients without Increasing the Risk of Stroke, Myocardial Infarction, or Death in a Large National Analysis. (December 2020) - Stone, David H.; Giles, Kristina A.; Kubilis, Paul; Suckow, Bjoern D.; Goodney, Philip P.; Huber, Thomas S.; Powell, Richard J.; Cronenwett, Jack L.; Scali, Salvatore T.
Abstract : Objective: Controversy persists regarding the use of protamine during carotid endarterectomy (CEA), despite real world evidence to support its use. The purpose of this study was to determine the impact of protamine reversal of heparin anticoagulation on the outcome of CEA in the USA. Methods: A prospective national registry (Society for Vascular Surgery Vascular Quality Initiative) of 72 787 patients undergoing elective asymptomatic CEA by 1879 surgeons from 316 centres in the USA and Canada from 2012 to 2018 was reviewed. Protamine use varied by both surgeon (20% rare use [< 10%], 30% variable use [11%–79%], 50% routine use [> 80% cases]) and geographical region (44% vs. 96%). Temporal trends in protamine use were also determined. End points included post-operative re-operation for bleeding, as well as potential protamine related thrombotic complications, including stroke, death, and myocardial infarction (MI). Predictors of end points were determined by multivariable logistic regression. Propensity matching was additionally used to control for differences between groups. Results: Of the 72 787 patients who underwent CEA, 69% received protamine, while 31% did not. Protamine use increased over time from 60% (2012) to 73% (2018). In total, 378 patients (0.7%) in the protamine treated group underwent re-operation for bleeding vs. 342 patients (1.4%) in the untreated cohort ( p < .001). Protamine use did not affect the rate of MI (0.7% vs. 0.8%; p = .023), stroke (1.1% vs. 1.0%; p = .20), or in hospital death (0.2% vs. 0.2%; p = 0.70) between treated and untreated patients, respectively. On multivariable analysis, protamine use was independently associated with reduced risk of re-operation for bleeding (odds ratio 0.5, 95% confidence interval 0.39–0.55; p < .001). Independent of protamine exposure, the consequences of a return to the operating room (RTOR) for bleeding were statistically significant, with a sevenfold increase in MI (RTOR 4.9% vs. no RTOR 0.7%; p < .001), an eightfold increase in stroke (RTOR 7.2% vs. no RTOR 0.9%; p < .001), and a 13 fold increase in death (RTOR 2.4% vs. no RTOR 0.2%; p < .001). Conclusion: Protamine reduces serious bleeding complications at the time of CEA without increasing the risk of MI, stroke, or death, in this large North American analysis. Based on this and previous regional work regarding protamine use in CEA, it is believed that there is now sufficient evidence to support its routine use, and it should be considered as a benchmark for quality during CEA.